IMPLEMENTASI BIMBINGAN KEAGAMAAN UNTUK MENINGKATKAN SEMANGAT IBADAH PADA REMAJA MASJID USWATUN HASANAH KELURAHAN PADANG MATINGGI RANTAU PRAPAT - Perkasa, Bagus; Madya, Efi Brata (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
This study aims to determine the Implementation of Religious Guidance to Increase the Spirit of Worship in Youth Mosque Uswatun Hasanah Padang Matinggi Village Rantau Prapat. This research uses a type of research that includes field research (filed research), using qualitative methods. The research location was chosen by researchers in Padang Matinggi Village Rantau Prapat. the time of this research was conducted on 20 June to 21 July 2023. The research informants consisted of 5 informants consisting of 1 cleric and 4 mosque teenagers. Data collection techniques in the form of interviews, observations and literature studies. Data analysis techniques using Miles dan Huberman techniques in the form of data reduction, data presentation and conclusion drawing and data validity in the form of triangulation of sources, techniques and time. The results of the study indicate that the implementation of religious guidance to increase the spirit of worship in uswatun hasanah mosque teenagers is very effective and has a significant influence on mosque teenagers where in this religious guidance is carried out with religious activities in the form of lectures / recitations, joint discussions / question and answer which are routinely held once a week, namely on Saturdays after isya' prayers, starting from 20.30 - 21.30 in the mosque. However, there are factors and supporters and obstacles in providing guidance to adolescents.